Development of Stop Bullying E-Book as an Effort by PAI Teachers in Growing Student Anti-Bullying Knowledge and Attitudes - Luthfiah Nur Eka Fauziah; Ani Nur Aeni; Dety Amelia Karlina (Elementary Teacher Education Program, Majalengka University, 2024)
The research is motivated by the bullying problem in elementary school students. The role of PAI subject teachers in shaping and teaching students' behaviour, morals, manners, and positive attitudes has a special and different touch. With the limited methods and media used to socialize students about the prevention of bullying and the inappropriate state and condition of libraries, as well as the very limited supply of books regarding bullying, the development of the e-book Stop Bullying is presented as one solution to help PAI teachers grow knowledge and attitudes toward anti-bullying in students. The research was carried out at SDN Bekasi Jaya IV, with the research subject being class 4B. Research and Development with the ADDIE (Analyze, Design, Development, Implementation, and Evaluation). Before being tested, the e-book Stop Bullying carried out a validation assessment by media experts and original material. The level of material validity obtained a total average percentage of (85.97%) and media validity of (93.12%). The e-book Stop Bullying received a teacher response rating with a total average percentage of 87.86%. After the trial and students carried out a test in the form of a questionnaire, the average rate of total knowledge obtained was (94.93%) and entered the very good category. The results of the attitude questionnaire obtained a total average percentage of (93.97%) and were included in the positive category. The E-Book Stop Bullying product can help PAI teachers cultivate anti-bullying knowledge and attitudes in students.Keywords: Development, E-Book, Bullying, Knowledge, Attitude